Sign in
Please select an account to continue using cracku.in
↓ →
If $$x = \frac{\sqrt{5} + 1}{\sqrt{5} - 1} and y = \frac{\sqrt{5} - 1}{\sqrt{5} + 1}$$, the value of $$\frac{x^2 + xy + y^2}{x^2 - xy + y^2}$$ is
$$x = \frac{\sqrt{5} + 1}{\sqrt{5} - 1} and y = \frac{\sqrt{5} - 1}{\sqrt{5} + 1}$$
$$ x+y = \frac{\sqrt{5} + 1}{\sqrt{5} - 1} + \frac{\sqrt{5} - 1}{\sqrt{5} + 1}$$
$$x+y =\frac{5+1+2\sqrt{5} + 5 + 1 -2\sqrt{5}}{5-1} $$
$$x+y = \frac{12}{4}$$ = 3
$$x\times y= \frac{\sqrt{5} + 1}{\sqrt{5} - 1} \times \frac{\sqrt{5} - 1}{\sqrt{5} + 1}$$ = 1
$$(x+y)^2 = x^2 +y^2 +2xy$$= $$(3)^2 = x^2 +y^2 +2$$
$$ x^2 +y^2 = 7 $$
$$\frac{x^2 + xy + y^2}{x^2 - xy + y^2}$$ {substituting $$x^2 +y^2 = 7 and xy =1$$
$$\frac{7+1}{7-1}$$ = $$\frac{8}{6}$$
= $$\frac{4}{3}$$
Create a FREE account and get: